Decision Making in the Implementation of Government in Makassar City, Indonesia (What is the Process?) - Arfiany; Guntur Suryo Putro; Hikmah; Laela Rosmawati; Pianti Sambo (www.amertainstitute.com, 2024)
The task of the government in every country is to achieve progress, from the lowest level to the highest, to achieve a more just, prosperous and advanced society. Decision making is one of the main responsibilities of managers in public bureaucracy. The aim of this research is to find out how the decision-making process is carried out in the Makassar city government. This research aims to identify, review, evaluate, and interpret research related to decision-making processes in organizations. With a Systematic Literature Review approach pattern in existing journals published in 2024. The research results show that the implementation of decision making currently focuses on three processes in the management function, namely: organizing, monitoring and the role of leaders as well as decision making in administration Makassar City Government is Good